DEVELOPING WORD WALLS AS MEDIA IN TEACHING WRITING SKILLS ON DESCRIPTIVE TEXT FOR SEVENTH GRADE STUDENTS AT MTS S NURUL HAKIM TEMBUNG - Sry Amalia; Sumarsih Sumarsih; Sisila Fitriany Damanik (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2018)
The aim of this study is to develop Word Walls as media for teaching writing descriptive text at the seventh grade students of MTs S Nurul Hakim Tembung. The researcher used Research and Development (R & D) method through six steps: gathering data and information, need analysis, media design, validating to experts, revising, and final product. The subjects of this research were 26 students from VII A at MTs S Nurul Hakim Tembung. The instrument of collecting data was using questionnaires and interviewing the teacher. The data were analyzed by descriptive text technique. The product was assessed from two experts. The average scores of the product assessment were 90 from English teacher, and 92 from English lecturer. The total average scores from two experts were 91 which was in very good quality. It means that the developed product/Word Walls is eligible to be used for teaching writing descriptive text for the seventh grades students at MTs S Nurul Hakim Tembung.  Keywords: Research and Development (R & D), writing descriptive text, word walls.